Synthesis of Metal (Ni) Doped Metal Oxide (ZnO) Heteronanostructures and Investigation of Their Morphological-Optical Properties - Mustafa Biçer (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
In this study, different volumes of Nickel (Ni) doped Zinc oxide (ZnO) thin films were deposited on FTO by hydrothermal method. The films were characterized by SEM, EDS, and UV-Vis Spectroscopy. When the SEM images were examined, the nanostructures showed different morphological features as the amount of doped (v) nickel-ZnO increased in comparison to undoped nickel-ZnO. Furthermore, it was demonstrated that the obtained film surface has a homogeneous distribution. EDS spectra showed the increase in Ni by volume and its presence in the film composition. The UV-Vis Spectroscopy results showed that Ni doping can change the transmittance and band gap values from 2.94 to 3.38, and thus the ZnO band gap can be adjusted by Ni doping. As a result of the findings, ZnO-NiO thin films are promising candidates for both high-performance hetero nanostructures and practical applications.